If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x+7)-6=15
We simplify the equation to the form, which is simple to understand
3(x+7)-6=15
Reorder the terms in parentheses
+(+3x+21)-6=15
Remove unnecessary parentheses
+3x+21-6=+15
We move all terms containing x to the left and all other terms to the right.
+3x=+15-21+6
We simplify left and right side of the equation.
+3x=0
We divide both sides of the equation by 3 to get x.
x=0
| -6t+12-3t=18 | | (3+10)+(-9)=13 | | 2-6x+5x=-10 | | 4w-2w+6=3w-12 | | 0.5x-3.7=0.3 | | 0.5x-3.7=0.7 | | (52+48+57+62+68+y)/6=59 | | (80+4).2=84 | | 90=2(7x+1)-3x | | 2x+12-x=14 | | 3(2x+9)=-18+33 | | -(4-x)=3/4(x+7) | | 10x-5=-8x+13 | | 304=-8(-6x+4) | | 6-(2x-8)=4-3x | | 14-3x=x+2 | | 14=7x-2x+9 | | x+x-150=180 | | -16+-10x=7x+18 | | 7-(4x-2)=8-5x | | 5+x-5x=-11 | | x+x/5=180 | | 15x+5x=6x | | 9(w-4)=8(7+w) | | 5.25Z-2.01=-8.94 | | 22+65=4+25 | | -34+3x=14-3x | | -8(x-8)-5=59 | | 8=-3x+2 | | 7(x-3)=7+6x | | 2x-6-3x=2 | | 15-.75g=13-50g |